2013
DOI: 10.3233/jad-121735
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-Dihydroxyvitamin D3 and Resolvin D1 Retune the Balance between Amyloid-β Phagocytosis and Inflammation in Alzheimer's Disease Patients

Abstract: As immune defects in amyloid-β (Aβ) phagocytosis and degradation underlie Aβ deposition and inflammation in Alzheimer’s disease (AD) brain, better understanding of the relation between Aβ phagocytosis and inflammation could lead to promising preventive strategies. We tested two immune modulators in peripheral blood mononuclear cells (PBMCs) of AD patients and controls: 1α,25(OH)2-vitamin D3 (1,25D3) and resolvin D1 (RvD1). Both 1,25D3 and RvD1 improved phagocytosis of FAM-Aβ by AD macrophages and inhibited fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 43 publications
6
100
1
1
Order By: Relevance
“…In accordance with our findings, some authors have reported an increase of IL-10 and IL-1ra, which should balance the higher in vitro production of pro-inflammatory cytokines [28,29]. However, some studies demonstrated a reduction of both pro-and antiinflammatory cytokines [30,31], suggesting a general impairment of immune functions in AD.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In accordance with our findings, some authors have reported an increase of IL-10 and IL-1ra, which should balance the higher in vitro production of pro-inflammatory cytokines [28,29]. However, some studies demonstrated a reduction of both pro-and antiinflammatory cytokines [30,31], suggesting a general impairment of immune functions in AD.…”
Section: Discussionsupporting
confidence: 79%
“…Ex vivo, LPS-and A␤-induced IL-10 production by PBMCs of AD patients and age-matched controls. PBMCs (3.10 6 cells / ml) from AD patients (n = 30) and age-matched controls (n = 18) were cultured either in complete medium alone (open symbol), supplemented with 1 ng/ml of LPS (full symbol, A) during two days or supplemented with a pool of three A␤ peptides: 1 g/ml of fragment (1-16), 10 g/ml of fragment (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), and 25 g/ml of fragment (1-40) (full symbol, B) during five days. Results have been showed as scatter plot and the median value is indicated by a black plain line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LXA 4 , and its analog aspirin-triggered LXA 4 , have also been shown to ameliorate the detrimental effects of A ␤ in vitro and in vivo ( 17,18,55 ), probably by increasing phagocytosis, downregulating proinfl ammatory signaling, and upregulating antiinflammatory cytokine production ( 11 ). RvD1 was also reported to enhance phagocytosis by macrophages ( 56 ). Thus, n-3 FA supplementation may favor the capacity of homeostatic functions to handle overabundance of A ␤ , as shown by preserved plasma TTR levels, SPM levels released by PBMCs, and an increased phagocytosis of A ␤ by microglia upon exposure to DHA and EPA in vitro ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the resolution pathway in maintaining normal cognition is suggested by the highlighted positive correlation between Mini-Mental State of Examination (MMSE) and the levels of RvD1 in the cerebrospinal fluid, suggesting that resolution can inhibit Alzheimer disease-related cognitive decline. Other studies published data reporting that a supplementation in n-3 PUFAs in patients with minor cognitive impairment increases RvD1 in macrophages (Fiala et al, 2015) and in vitro RvD1 with vitamin D promotes Aβ-phagocytosis in isolated Alzheimer's patient macrophages (Mizwicki et al, 2013). A study of Harrison et al (2015) demonstrates that RvE1, administered intraperitoneally for consecutive days, decreases the traumatic brain injury-induced activation of microglia.…”
Section: Actions Of Resolvins In the Central Nervous Systemmentioning
confidence: 97%